PENGARUH KOMISARIS INDEPENDEN, KOMITE AUDIT, KUALITAS AUDIT, DAN BUDAYA PERUSAHAAN TERHADAP TAX AVOIDANCE - Leonardus Tri Nugroho, (2021)
This study aims to determine the effect of independent commissioners, audit committees, audit quality, and corporate culture on tax avoidance in 142 manufacturing sector companies listed on the Indonesia Stock Exchange for the 2016-2019 period. This research is a type of quantitative research using secondary data in the form of the company's annual report. The Common Effect Model (CEM) with panel data regression was used in this study using STATA version 16. Based on the test results and analysis, it can be concluded that independent commissioners and gender diversity have a significant positive effect on tax avoidance, while audit committee, audit quality, and power distance has no effect on tax avoidance. The results of this study have implications for companies, regulators and future researchers.